BLOOD TYPES AND CARCINOMA CUTIS: BLOOD TYPES AND CARCINOMA CUTIS - Todorov, Velislav; Boycheva, Maria; Minkov, Cvetan; Georgieva, Rada; Boichev, Milen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The present study included 101 patients with Ca cutis (76 men and 25 women). The patients’ blood group affiliation to the AB0 and Rhesus factor systems was monitored. There was a statistically significant increase in the disease in patients with 0 blood group (p <0.05) and a slight increase in the patients with AB blood group, when compared with the control group of healthy people. The incidence of the condition is reported in the other groups with varying degrees of decrease, which was significant in group A (p <0.05). It has been found that the disease is much more common in our country compared to its levels in Europe (65,1 / 100000 in men and 52,4 / 100000 in women compared to 18,2 / 100000 in men and 8,3 / 100000 in women respectively). No significant differences were observed in the Rhesus factor system compared to the control group.